ANALISIS PENGAMPUNAN PAJAK (TAX AMNESTY) PADA KANTOR PELAYANAN PAJAK MAKASSAR BARAT - Andi Lutfi; Bakari, Friansyah; Basar, Nur Fatwa (Komunitas Manajemen Kompetitif, 2025)
This research aims to describe the amount of tax revenue, before and after tax amnesty. This research uses quantitative data. The data source used is secondary data, namely the realization of tax revenues and the number of taxpayers at the West Makassar Primary Tax Service Office in 2015-2017 and 2021-2022. The analytical method used is descriptive quantitative, namely explaining tax revenues before and aftertax amnesty. The research results show that the government's tax amnesty program increases tax revenues at the West Makassar Primary Tax Service Office